Sistem Intelijen Bisnis Pada Jasa Ojek Online - Achmad Fauzi; Fadhli Nursal; Agung Setiawan; Ayu Diah Puspita; Fany Lathifatul S; Sahira Salfaniz; Willy Jovadi Wijaya; Adam Surachman (Jurnal Portofolio : Jurnal Manajemen dan Bisnis, 2023)
The most common type of ordinary transportation is ojek, which is a motor vehicle available for use by ordinary people with a certain amount of money paid as a deposit against the services provided. The steps taken in this study are the collection of information or theories collected from the literature in the Google Scholar online journal articles related to this article. The results of this study will be a source for distributing problems that often cause conflicts that compare the old transportation provision model and the new model (technology-based). From the results above, it can be seen that changes in business information affect the growth of customer satisfaction. This is reflected in the meaning of business intelligence which is greater than the level of meaning used. And because this is also reflected in the coefficient of business determination